2016
DOI: 10.1542/peds.2015-0879
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case Report of Immobility-Induced Hypercalcemia in an Infant

Abstract: Immobility-induced hypercalcemia is a rare cause of hypercalcemia in children, and to our knowledge it has never been reported in an infant. Infants and children are in a state of high bone turnover. Therefore, they are prone to the imbalance of osteoblastic and osteoclastic activity that occurs with prolonged immobilization, leading to hypercalcemia. Here we present the case of an infant with hypercalcemia who presented with fatigue, irritability, and failure to thrive after prolonged immobilization. Therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Albright also reported that the skeletal structure was exposed to many stresses, hormonal and nutritional effects during normal activity (10). Excessive reduction in mechanical stress on the bone reduces osteoblast-mediated bone formation and accelerates osteoclast-mediated bone absorption (8,9). During this separation of bone formation, and resorption, a minority of patients develop severe hypercalcemia, which can affect renal…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Albright also reported that the skeletal structure was exposed to many stresses, hormonal and nutritional effects during normal activity (10). Excessive reduction in mechanical stress on the bone reduces osteoblast-mediated bone formation and accelerates osteoclast-mediated bone absorption (8,9). During this separation of bone formation, and resorption, a minority of patients develop severe hypercalcemia, which can affect renal…”
Section: Discussionmentioning
confidence: 99%
“…Although this is rare among patients who can move freely, immobilization can be a cause of hypercalcemia among patients in the intensive care unit. Differential diagnosis of hypercalcemia includes hyperthyroidism, infection, inflammatory processes, prolonged immobilization (>2 weeks), or malignant tumors [ 1 , 3 , 8 ]. Immobilization-induced hypercalcemia is rare in healthy individuals, although it can occur in adolescent males, especially after a fracture [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the cases were described in adult patients, however it was noted that this condition is more common in children and adolescents in whom bone turnover is high. One literature described a rare case of immobility-induced hypercalcemia in a 2-month-old female infant [2]. The management of hypercalcemia depends on the level of severity.…”
Section: Discussionmentioning
confidence: 99%
“…Infants and children are in a state of high bone turnover. Therefore, they are prone to the imbalance of osteoblastic and osteoclastic activity that occurs with prolonged immobilization, leading to hypercalcemia [2]. Immobilization hypercalcemia diagnosis requires an evaluation to rule out hypercalcemia causes.…”
Section: Introductionmentioning
confidence: 99%